Saúde mental em servidores públicos do Tribunal de Justiça da Paraíba após pandemia de Covid-19 - Souza, Éverton Procópio (2024)
This dissertation has an epidemiological, exploratory, quantitative and transversal design, with the general objective of analyzing the mental health of public servants at the Paraíba Court of Justice after the COVID-19 pandemic. Between April and May, 2023, an online protocol was applied with the sociodemographic questionnaire and the Depression, Anxiety and Stress Scale (DASS-21), culminating in three studies. 194 public servants participated, with an average age 47 year-olds (SD = 8.3 years); majority female (55.7%). The first study checked for symptoms of depression and anxiety. Descriptive and inferential statistical analyzes were performed. 47.9% expressed symptoms of depression and 49.6% symptoms of anxiety, ranging from mild to extremely severe levels. 75.8% were infected by COVID-19. At the significance level of p < 0.10, symptoms of depression were associated with the variables skin color (p = 0.07) and length of service (p = 0.06). The gender variable was associated with anxiety (p = 0.10). People who had been infected by COVID-19 did not show a significant association with symptoms of depression (p = 0.12) and anxiety (p = 0.44). The presence of depression and anxiety among public servants of the Paraíba judiciary had high levels. The evidence demonstrated that the contamination by COVID-19 was not statistically related to the existence of depressive and anxious symptoms. The second study investigated stress levels. Multivariate statistical techniques, multiple comparison analysis were used and the thresholds of the items of the DASS-21 stress subscale were estimated using Item Response Theory. 36.6% of employees had stress within the normal range; 34.4% of them had mild symptoms; 15.5% had moderate symptoms; 10.3% had severe symptoms; and 7.2% had more severe symptoms of stress. COVID-19 diagnosis, post-COVID status, insufficient sleep, and overwork were associated with higher levels of stress. The physical activity variable was associated with low levels of stress. The high stress of public servants is associated with factors related to COVID-19 and the time dedicated to work, while physical activity is associated with lower stress scores. The third study verified how symptoms of depression, anxiety and stress influence each other and which symptoms act as bridges between these groups. Network analysis was used to map symptom tracked by DASS-21. The stress items “difficult to calm down”, “feeling that I was always nervous”, “feeling agitated” and “finding it difficult to relax” were central symptoms in the activation of symptoms of depression and anxiety. “Feeling that I was a little emotional/sensitive” from the stress community points to an activator for the co-occurrence of depressive and anxious symptoms. The network analysis identified the influence between DASS-21 symptoms of depression, anxiety and stress, highlighting specific symptoms of stress that can act as a bridge for the concomitant occurrence of depressive and anxious symptoms. Through different analyzes it was possible to investigate the correlation between symptoms of depression, anxiety and stress tracked by DASS-21 and advance the understanding of the mental health of public servants in the Paraíba judiciary.